Effect of fatty acid methyl ester polyoxyethylene ether on the rheological properties of cement filled with artificial marble waste powders. (15th December 2021) - Li, Hai; Ji, Dewei; Chen, Chenggang; Wang, Xiaohong; Tu, Jinchun; Zhang, Kexi; Ding, Aiwu
Abstract: The disposal of artificial marble waste powder (AMWP) with unsaturated polyester presents a serious problem. This problem can be effectively addressed by using AMWP to replace parts of cement in concrete. However, the rheological properties of an AMWP–cement slurry are considerably affected by the unsaturated polyester in AMWP. This study aims to use fatty acid methyl ester polyoxyethylene ether (FMEE) as an admixture in AMWP–cement cementitious materials to improve the rheological properties of the AMWP–cement system. The fluidity, rheological properties, and mechanical properties of the AMWP–cement system to which different concentrations of FMEE were added were evaluated. Laser particle size analysis, thermogravimetric analysis, Fourier-transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy were also conducted to identify the mechanism allowing AMWP to affect the rheological properties of the cement paste and determine the effect of FMEE on improving the rheological properties. Results indicate that the adsorption of polycarboxylate (PCE) superplasticizers on cement particles in the AMWP–cement system is heavily influenced by polyethylene terephthalate in AMWP. The addition of FMEE competes with the adsorption of PCE on AMWP. FMEE with a robust adsorption capacity is then preferentially adsorbed on AMWP, such that the PCE with no adsorption sites is adsorbed on cement particles, thus improving the rheological properties of the cement slurry. Meanwhile, the pores generated by FMEE and AMWP affect cement hydration, in addition to the formation and bonding of hydration products. These two factors reduce the mechanical properties of the cement mortar.